Battery energy storage system state-of-charge management to ensure availability of frequency regulating services from wind farms. (November 2020) - Boyle, James; Littler, Timothy; Foley, Aoife
Abstract: State of charge management in battery energy storage systems will be imperative to ensure that frequency regulating services can be provided when required. Two state of charge controllers are proposed as a comparison analysis in this research. One controller was designed to meet the charge/discharge requirements imposed on assets providing enhanced frequency response. This controller makes small corrective changes to the battery's power output to restore nominal charge. Simulation results show that the controller is effective at restoring nominal charge when the deviation from nominal is small. However, when the charge is significantly high or low, operating within the confines of the enhanced frequency response service envelope will lead to long periods where the charge is above or below nominal. This will reduce the availability of frequency regulating services from the system. A second controller is proposed to accelerate the restoration of nominal charge. This controller is intended for use in wind farms that have an integrated battery energy storage system, whereby hybrid dispatch control can be employed. The objective of hybrid control is to create a power exchange between the wind turbine and battery system to accelerate nominal charge restoration, without significantly impacting system frequency and the wind farm's output. Highlights: An IEEE 39 bus testbed with type 3 turbine and battery was built in PowerFactory. Frequency simulations were ran with a fuzzy logic and accelerated charge controllers. Fuzzy controller operated within the confines of enhanced frequency response envelope. Optimum charge was achieved 5 times faster with accelerated charge restoration. Results indicate that hybrid systems can accelerate charging to improve availability.